Stationary Interference Cancellation in Upstream Coordinated DSL Using a Turbo-MMSE Receiver - Issam Wahibi; Meryem Ouzzif; Jérôme Le Masson; Samir Saoudi (International Journal of Digital Multimedia Broadcasting)
We investigate the scenario of an upstream coordinated DSL transmission in presence of spatial-correlated noise. Joint signal processing helps mitigate this noise and reduce internal interference effects between coordinated users. We propose to couple noise whitening with a mean-squared error iterative receiver in order to approach the matched filter bound of the DSL coordinated system. The convergence of the iterative scheme in this scenario is predicted using EXIT charts under realistic transmission conditions.